a Taskboard System Based On Website (Case Study: CV Nukegraphic Indonesia) - Ceng Giap Yo; Dennie Dennie (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2018)
CV. Nukegraphic Indonesia as one of the fast growing website in Indonesia would require a lot of support, including support in the field of Information Technology. Recording task list that still use manual systems, often prevent the processing of information about the details of the status of the task and the status of projects ongoing or already completed in the form of a percentage of each project, as well as recording task that still use paper media is also considered only will lead to waste in paper usage. Recording task that is only made in the scope of the company's staff also hinder the work process of the company when staff are outside the company. The method used in the manufacture of a web-based application taskboard this form of collecting data through observation and questionnaires were distributed in the scope of the company. The test results of these applications concluded that with the application taskboard-based website is an account executive can find out information about the details of the status and the status of the project in a short time, because the data processing has been made into a computerized provided through the application, both an account executive and members are also more easy in knowing the task that must be done even though it is outside the company. With this application is expected to help the performance of employees in a company to be more productive